Systemic chemotherapy with epirubicin for treatment of advanced or multifocal hepatocellular carcinoma - Pohl, Jürgen; Zuna, Ivan; Stremmel, Wolfgang; Rudi, Jochen (Chemotherapy, 2001)
The purpose of this retrospective study was to determine the response rate and effect on survival of chemotherapy with epirubicin in non-resectable advanced hepatocellular carcinoma (HCC).
Gesehen am 09.09.2021